Between Banat : queer Arab critique and transnational Arab archives - Shomali, Mejdulene Bernard, 1982- (Duke University Press, 2023)
"Between Banat presents a feminist and queer of color analysis of homoeroticism and nonnormative sexualities between Arab women as represented in transnational Arab literature, art, and film. It draws on a dynamic archive of Arabic and Anglophone film and literature, as well as works in translation and transliteration to outline dominant discourses which make representing queer Arab subjects difficult. Between Banat establishes queer Arab critique as a strategy to read around limiting discourses and proposes tenets to make possible queer Arab futures. Mejdulene Bernard Shomali demonstrates how systems of heteropatriarchy, Arab nationalisms, and Orientalism work in relation to mire queer Arab women's horizons and uses queer Arab critique to locate queer desire amidst heteronormative imperatives."--